In Front of the Distorting Mirror of the Vortex: the Reception of Vorticism in the British Political Press (1913-1916) - Oriane MARRE (E-REA)
The Vorticist movement appeared in 1914, after a fight between the English avant-garde and Italian Futurism, just as England entered World War One, and when the country was facing an uneasy transition from an old and stable order to a new era of trouble reinforced by different strikes conducted by suffragettes, Unionists and workers. The arrival of Marinetti in London in November 1913 had already triggered some interest among political journalists who questioned the consequences of that “Italian invasion”, and the Vorticist movement, born on June 11th 1914, increased their worries by its alleged violence. However, during the war, the appreciation of the avant-garde by political journalists changed: artists became a mirror of the change within British society and Vorticists’ works became closely linked to the enlistment of the artists. The vision of these works by political journalists illustrates how political parties reacted to the war: they linked Vorticist abstract research to the unbearable decline of humanity and civilization.